Identification and functional analysis of cyotochrome P450 from Bacillus lehensis G1 - Ang, Swi See (2016)
Cytochrome P450s (CYPs) are a superfamily of heme monooxygenases which catalyze a wide range of biochemical reactions. The reactions involve the introduction of an oxygen atom into an inactivated carbon of a compound which is essential to produce an intermediate of a hydroxylated product. Vitamin D 25- hydroxylase catalyses the first step in vitamin D biosynthetic pathway, essential in the activation of vitamin D. Several types of CYPs had been found as potential 25-hydroxylases. However, most of them originate from eukaryotes and are membrane associated proteins. A putative gene sequence encoding a CYP, termed CYP107CB2 was found in the genome of a new isolate Bacillus lehensis G1, and this gene shared sequence identity with the bacterial vitamin D hydroxylase (Vdh) from Pseudonocardia autotrophica. In order to deepen the understanding on the properties and biological function of CYP in B. lehensis G1, the objective of this study was to mine for a novel CYP from B. lehensis G1 with hydroxylase activity on vitamin D metabolites. Computational methods to search for the novel CYP from CYP structural databases were employed to identify the conserved pattern, functional domain and sequence properties of the uncharacterized CYP from B. lehensis G1. The CYP107CB2 gene was isolated and amplified using PCR and the CYP107CB2 protein was over-expressed in E. coli Rosetta-gami (DE3) followed by enzyme purification via single step affinity chromatography. The biological properties and possible functions of CYP107CB2 were characterized through absorption spectral analysis and were assayed for vitamin D hydroxylation activity. Optimization and CYP characterization were conducted to increase the turnover of hydroxylated products with an NADPH-regenerating system. Crystallization trials on CYP107CB2 protein were conducted via preliminary screening with Crystal Screen I and II through vapour-diffusion sitting drop method. Sequence analysis studies indicated that CYP107CB2 contained the fingerprint heme binding sequence motif FxxGxxxCxG at amino acid position 336-345 as well as other highly conserved motifs characteristic of CYP proteins. Docking studies showed several potential substrates, including vitamin D3, 25-hydroxyvitamin D3 and 1α- hydroxyvitamin D3, were located proximally to the enzyme’s heme center. The over-expressed CYP107CB2 protein was dominantly in cytosolic and the purified fraction showed a protein band at approximately 62 kDa on SDS-PAGE, representative for CYP107CB2. Spectral analysis demonstrated that the protein was properly folded and it was in its active form. HPLC and MS analysis on the product from a reconstituted enzymatic reaction confirmed that CYP107CB2 converted vitamin D3 and 1α-hydroxyvitamin D3 into 25-hydroxyitamin D3 and 1α,25-dihydroxyvitamin D3, respectively. CYP107CB2 formed crystal in formulation No. 38 from Crystal Screen II comprising 20% (v/v) PEG 10 000 and 0.1 mM HEPES buffer pH 7.5. In conclusion, a novel CYP107CB2 was identified from B. lehensis G1 and these findings proved that CYP107CB2 is a biologically relevant vitamin D3 25-hydroxylase.